Penerapan Pembelajaran Mendalam untuk Penguatan Kompetensi Design Thinking Siswa SMK Muhammadiyah 2 Tangerang Selatan - S, Sahrudin; Putri, Dianasyah; Pratama, Hady Putra; M, Masitoh; Harahap, Nursakina; Katulistiwasari, Puri; Jaya, Herdi Wisman (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The low level of critical and creative thinking skills among vocational high school students has contributed to the high rate of open unemployment. This community service program aimed to strengthen students’ design thinking competence at SMK Muhammadiyah 2 Tangerang Selatan through a deep learning approach. The activity employed a participatory, project-based training method consisting of the stages of empathize, define, ideate, prototype, and test. The results showed an improvement in students’ understanding of design thinking, active participation, and ability to generate solutions to real-world problems within the school environment. This program also contributed to strengthening the Pancasila Student Profile, particularly in critical reasoning, creativity, collaboration, and independence.